2010
DOI: 10.1108/17506121011059777
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical innovation and generic challenge: recent trends and causal factors

Abstract: PurposeThis paper aims to analyze the present trends in pharmaceutical innovation and the impact of generic competition.Design/methodology/approachA secondary research was conducted to collect data related to new drug approvals of various classes over previous years; trends of investment in research and development; and the pipeline of new drug products of pharmaceutical companies.FindingsWhile the new molecular entity (NME) approval rate has not improved over previous years, innovators have been aggressively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Though Das (2004) found that overall R&D spending has decreased, Dubey and Dubey (2010) noted that spending by R&D centers set up as wholly owned subsidiaries (or partnerships) by MNEs in India has increased. For example, Singh (2006) noted that Chakrabarti and Bhaumik (2009) found that United States (US) MNEs have driven recent growth in patenting from India.…”
Section: Macro/outcome Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Though Das (2004) found that overall R&D spending has decreased, Dubey and Dubey (2010) noted that spending by R&D centers set up as wholly owned subsidiaries (or partnerships) by MNEs in India has increased. For example, Singh (2006) noted that Chakrabarti and Bhaumik (2009) found that United States (US) MNEs have driven recent growth in patenting from India.…”
Section: Macro/outcome Studiesmentioning
confidence: 99%
“…Some studies have specifically examined the link between R&D investment and innovation. For example, Dubey and Dubey (2010) found that despite increased R&D spending, Indian pharmaceutical firms have not seen a substantial increase in their drug pipeline and approval of new molecular entity (NME) rate, though there has been an increase in incremental innovations and applications for new drug approvals. Some studies in this group also looked at the moderating factors that influence the link between R&D and innovation outcomes.…”
Section: Micro/outcome Studiesmentioning
confidence: 99%
“…Acemoglu and Linn 28 compared NME approvals from 1970 to 2000 in the United States to rates of all nongeneric drug approvals, finding that NME approvals made up 20% of all nongeneric drug approvals during the study period (442/2,203). Dubey and Dubey, 29 by contrast, compared rates of NME approvals to “incremental innovations,” which they defined as rates of approval of new drug formulations, such as differing esters or salts, and fixed combinations of already approved active ingredients. They found that even though the rate of NME approvals declined during the study period (1999–2008), the rate of such “incremental innovation” increased.…”
Section: Taxonomy Of Studies Assessing Drug Innovationmentioning
confidence: 99%
“…Generic pharmaceuticals have conditioned the business of pharmaceutical invention. Recognising the greater uncertainty of radical innovations, mostly when compared to the business efficiency of generic drug production, innovator companies have discovered incremental innovation to enhance the market life of their existing high-selling products (Dubey and Dubey, 2010). Mazumdar-Shaw (2018) emphasised that affordable innovation provides means to invent, be flexible and do more with less.…”
Section: Issues and Challenges In The Indian Pharmaceutical Industrymentioning
confidence: 99%